Management of diabetic ketoacidosis in internal medicine: insulin protocols, electrolyte balance, and clinical outcomes - Alharbi, Samar Abed; Meshari, Amjad Mohammed; Henawi, Zainab Abdulaziz; Alsaadi, Reem Mohammed; Alqarni, Shaher Saad; Hani, Ali Fuad Al; Alhamrani, Ola Hussain; Saptan, Laila Mohammed; Hamoud, Zainab Abduljabbar Al; Alshanbri, Nawaf Khalid; Jafar, Zainab Abdulmonem; Farag, Abdelrahman (International Journal Of Community Medicine And Public Health, 2023)
Diabetic ketoacidosis (DKA) is a critical complication of diabetes mellitus (DM), characterized by hyper-glycemia, acidosis, and ketosis. It poses a substantial risk of morbidity and mortality, especially in type 1 DM patients. DKA can be triggered by various factors, including insulin deficiency, infections, alcohol abuse, and other medical conditions. Hospital admissions for DKA are increasing, with mortality rates of up to 5-9%, often linked to severe underlying illnesses and complications such as myocardial infarction and stroke. Effective DKA management involves rehydration, correction of electrolyte imbalances, insulin administration, and addressing precipitating factors. Fluid resuscitation with isotonic saline is vital to restore hydration, and continuous intravenous insulin infusion is the preferred method to control blood glucose and suppress ketone production. Electrolyte imbalances, particularly potassium, sodium, phosphate, and magnesium, require careful monitoring and correction. Clinical outcomes in DKA management include resolving acidosis, normalizing blood glucose, and restoring electrolyte balance, all while achieving and maintaining clinical stability. Complications like cerebral edema and acute respiratory distress syndrome can significantly impact the prognosis. Long-term considerations encompass diabetes management, patient education, and follow-up care.